MARKETPLACES AS A KEY DRIVER OF GLOBAL E-COMMERCE - Yarova, Inessa; Yurchenko, Anastasia (Socio-economic relations in the digital society, 2023)
Currently, e-commerce is becoming a modern challenge to accelerate the development of the global economy. This requires the introduction of qualitatively new approaches to the strategic management of activities using information technology. The purpose of this article is to study the key issues, features and trends in the development of e-commerce in the context of international business digitalisation on the example of international online marketplaces.This paper analyses the risks and benefits, distribution logistics issues for the development of e-commerce, and its positive and negative impact on trade in general. It is determined that today the pace of development of e-commerce is very fast, significantly exceeding the pace of development of traditional trade.An important indicator of a successful e-commerce business strategy is a clear vision and implementation of the strategy of involving marketplaces in the trading strategy. A clear understanding of which marketplace best suits the needs of the business and competent implementation significantly increases the chances of making a quick profit in online trading. The article notes that the business model of marketplaces is considered to be promising, as it is beneficial for both the seller and the buyer. This paper considers the key and most well-known globally recognized marketplaces such as Amazon, eBay and Etsy, their main advantages and disadvantages, comparative characteristics of marketplaces and how to effectively integrate products into these tools, as well as the future implications of these concepts for distribution logistics in the context of e-commerce.
Keywords: e-commerce; marketplace; distribution logistics; digitalization; risks